PENGARUH EKUITAS MEREK TERHADAP LOYALITAS MEREK PRODUK APPLE SMARTPHONE DENGAN KEPUTUSAN PEMBELIAN SEBAGAI VARIABEL MEDIASI - Yulyaningsih, Veronika Bella; Fitriana, Ana; Listiana, Erna; Ahmadi, Ahmadi (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This study aims to analyze the influence of brand equity on brand loyalty of Apple products (iPhone), with purchase decision as a mediating variable. Brand equity in this research is measured through three main indicators: brand trust, brand image, and perceived quality. A quantitative approach was used, employing a survey method involving 120 iPhone users in Pontianak City, selected through purposive sampling. Data were collected using a 5-point Likert scale questionnaire and analyzed using SmartPLS 4.0 software. The results indicate that brand trust, brand image, and perceived quality significantly influence brand loyalty, both directly and indirectly through purchase decision. The purchase decision is proven to be a significant mediator in the relationship between independent variables and brand loyalty, with the R-square value for brand loyalty reaching 0.633. These findings highlight the importance of brand equity strategies in shaping customer loyalty and emphasize the role of purchase decisions in strengthening consumers' emotional attachment to the iPhone brand. This study provides both theoretical and practical contributions to marketing strategy development in the premium smartphone industry.